2008
DOI: 10.1038/oby.2008.284
|View full text |Cite
|
Sign up to set email alerts
|

Fueling the Obesity Epidemic? Artificially Sweetened Beverage Use and Long‐term Weight Gain

Abstract: articles epidemiologyWe summed AS soda, coffee, and tea intakes to estimate AS beverage (ASB) consumption, and-among consumers-identified ASB consumption quartiles. Participants using AS sweeteners and/or cereals-but not ASBs-were included in ASB consumption quartile 1. Participants reporting no AS use were categorized "nonusers. "Dieting status and exercise frequency (2) were recorded at baseline and follow-up. In cohort 1 only, baseline 24-h dietary recalls were performed (2). In cohort 2 only, follow-up AS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
311
4
15

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(348 citation statements)
references
References 50 publications
18
311
4
15
Order By: Relevance
“…Explanation (2) could be supported by previous observational studies suggesting an association between non-caloric sweeteners and consumption of artificially sweetened beverages and weight gain [25,26], although recent randomised trials conducted in children and adolescents do not support this hypothesis [27,28].…”
Section: Discussionmentioning
confidence: 50%
“…Explanation (2) could be supported by previous observational studies suggesting an association between non-caloric sweeteners and consumption of artificially sweetened beverages and weight gain [25,26], although recent randomised trials conducted in children and adolescents do not support this hypothesis [27,28].…”
Section: Discussionmentioning
confidence: 50%
“…Adjusted cardiac event models were stratified on hypertension, and high cholesterol and adjusted mortality models were stratified on hypertension and the history of diabetes because these variables did not meet the proportional hazards assumption ∥ The majority of loss of patients in model 4 was secondary to missing data for salt intake and calibrated energy HR hazard ratio, CI confidence interval *Model IV: Adjusted for age, race, education, income, smoking status, BMI, diabetes, hypertension, hyperlipidemia, alcohol intake, log calibrated energy intake, physical activity, sugar-sweetened beverage intake, salt intake, and hormone therapy † Model IV; Included women without a history of diabetes, hypertension, and high cholesterol ‡ Adjusted for Model IV excluding salt intake and calibrated energy intake § Adjusted for Model IV including Healthy Eating Index-2005 scores and excluding salt intake and calibrated energy intake increase in BMI with increasing intake of artificially sweetened beverages, with an apparent dose response relationship between the amount of artificially sweetened beverages consumed and weight gain. 7 As both metabolic syndrome and obesity are important risk factors for CVD, this may contribute in part to the higher incidence of CVD events in this population.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several population-based studies have demonstrated a positive association between diet drinks and the metabolic syndrome, which in turn is associated with increased risk for CVD. 2,[7][8][9] However, data are limited as to whether there is an increased CVD risk associated with diet drink consumption. Given the large population directly affected by such an association, this study was performed to evaluate the effect of diet drink consumption on CVD outcomes in the Women's Health Initiative Observational Study (WHI OS) cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effect of ASSD on appetite and energy intake has been discussed intensively (Rolls, 1991;Rogers and Blundell, 1993). Even though some results showed body weight reducing effects of ASSD compared with SSSD (Raben et al, 2002), increased consumption of ASSD has not had the expected moderating impact on the obesity epidemic (Fowler et al, 2008). Previous studies have suggested that ASSD may lead to increased hunger sensation due to the sweet taste unaccompanied by calories (Mattes and Popkin, 2009).…”
Section: Introductionmentioning
confidence: 99%